67.8k views
4 votes
Please help and explain how to do this

Please help and explain how to do this-example-1
User Thao
by
5.5k points

1 Answer

5 votes

Answer:

4√3

Explanation:

The distance formula applies. It tells you ...

distance = √((x2 -x1)² +(y2 -y1)²)

Filling in the given values, you have ...

distance = √((-√32 -(-4√2))² +(2√3 -(-√12))²)

= √((-4√2+4√2)² +(2√3 +2√3)²)

= √(0 + (4√3)²)

distance = 4√3

___

We make use of the fact that ...


a√(b)=√(a^2b)\\\\√(32)=√(16\cdot 2)=4√(2)\\\\2√(3)=√(2^2\cdot 3)=√(12)

User Lisa Miskovsky
by
6.4k points